When we speak about gravitons, we tend to generally think about a metric perturbation of the form:

[math]g = g + h[/math]

where [math]h[/math] is the metric fluctuation that can be considered as the graviton.

Isn't h just joule time? then g is Newtons per kilograms. Well, I got this to Joule * time^{2} so are you saying that should be only time.

∇E_{b}(t,ω,R,M,I) = ∇(1/((1-(((2M_{b}G / R_{s}) - (I_{s}ω_{s}^{2}/2M_{b}))^{2}/C^{2}))^{1/2}))M_{b}C^{2}

Well, removed the Laplace operator from both sides then like the cosmology post for Static Non Moving objects through space. This situation not caring about exact position or number of many objects with many parts.

E_{b}(t,ω,R,M,I) = (1/((1-(((2M_{b}G / R_{s}) - (I_{s}ω_{s}^{2}/2M_{b}))^{2}/C^{2}))^{1/2}))M_{b}C^{2}

ΣE_{b1}Δt^{2}_{1⇒∞}(t,ω,R,M,I) = E_{b}_{1}Δt^{2} + E_{b}_{2}Δt^{2}_{2}+........... + E_{b}_{∞}Δt^{2}_{∞}

This would be Graviton Frequency for an object that is exiting or entering the universe or Teleporting not moving through time linearly that extra dimension of time has been added into this equation. Those pesky time travelers, Inter-dimensional travelers, or Teleporting objects being the "Blink". This also handles "Quantum Erasure" destruction of Energy-Mass from the universe or "Quantum Fluctuation" generation of Energy-Mass into the universe from whatever source.

Σg = ΣE_{b}(t,ω,R,M,I) /hM

If your object does move through time linearly it would be.

Σg= ΣE_{b}(t,ω,R,M,I)/hM

which does satisfy this equation either way for fluctuation caused by gravitons from one object with one part or one object with many parts.

Σg_{2} = gravitons received from external object with one part or object with many parts.

g_{1} = gravitational acceleration received from self.

Σg = g_{1} + Σg_{2}, being sum of all gravitational acceleration, from self and object with one part or object with many parts.

Σg = g_{1} + Σg_{2} = g + ΣE_{b}(t,ω,R,M,I) /hM = g +ΣE_{b}(t,ω,R,M,I)/hM

If you had an object that was non static moving object through space then the equation would be.

E_{b}(t,ω,R,M,I) = (1/((1-(((2M_{b}G / R_{s}) - (I_{s}ω_{s}^{2}/2M_{b})+V)^{2}/C^{2}))^{1/2}))M_{b}C^{2}

Then for Non static many moving objects with many parts would be.

∇E_{b}(t,ω,R,M,I,x,y,z) = ∇(1/((1-(((2M_{b}G / R_{s}) - (I_{s}ω_{s}^{2}/2M_{b})+V)^{2}/C^{2}))^{1/2}))M_{b}C^{2}

Σ∇g_{2} = gravitons received from external many objects with one part or many objects with many parts.

g_{1} = gravitational acceleration received from self.

Σ∇g = g_{1} + Σ∇g_{2} , being sum of all gravitational acceleration, from self and many objects with one part or many objects with many parts.

Σ∇g = g_{1} + Σ∇g_{2} = g + Σ∇E_{b}(t,ω,R,M,I,x,y,z)/hM = g +Σ∇E_{b}(t,ω,R,M,I,x,y,z) /Mh

Δg = Σ∇g

Then

g_{1} = Δg - Σ∇g_{2}

Σ∇g_{2} = Δg - g_{1}

So, this was already calculated into the original equation.

I think these were the forms you were looking for unless g was supposed to be g(u,v) but I took those as Gravitational acceleration.

**Edited by Vmedvil, 05 January 2018 - 08:29 AM.**